Cross-Correlation of Heart Rate and Oxygen Saturation in Very Low Birthweight Infants: Association with Apnea and Adverse Events - Fairchild, Karen D.; Lake, Douglas E. (American Journal of Perinatology, 2018)
Background Analysis of subtle vital sign changes could facilitate earlier treatment of acute inflammatory illnesses. We previously showed that high cross-correlation of heart rate and oxygen saturation (XCorr-HR-SpO2) occurs in some very low birthweight (VLBW) infants with sepsis, and hypothesized that this corresponds to apnea.Methods In 629 VLBW infants, we analyzed XCorr-HR-SpO2 in relation to central apnea with bradycardia and desaturation (ABD), BD with or without central apnea (BD), and percent time in periodic breathing (PB) throughout the neonatal intensive care unit (NICU) stay (75 infant-years). We reviewed 100 days with extremely high XCorr-HR-SpO2 (>0.7) and control days for clinical associations. Next, we identified all cases of late-onset septicemia (LOS) and necrotizing enterocolitis (NEC) and analyzed change in XCorr-HR-SpO2 before diagnosis.Results Mean XCorr-HR-SpO2 was ∼0.10, and increasing XCorr-HR-SpO2 was associated with increasing ABD, BD, and PB (correlation coefficients >0.93). Days with maximum XCorr-HR-SpO2 >0.7 were more likely to have an adverse event than control days (49% versus 13%). In 93 cases of LOS or NEC, there was a 67% increase in XCorr-HR-SpO2 in the 24-hour period prior to diagnosis compared with the previous day (p < 0.01).Conclusion High XCorr-HR-SpO2 is associated with apnea and adverse events including LOS and NEC.
Keywords: sepsis; necrotizing enterocolitis; apnea; biomarker; periodic breathing; vital signs; entrainment; cross correlation